A Polícia em Guerra: a ditadura e a Polícia Militar em São Paulo (1964-1982) - Nascimento, Gabriel dos Santos [UNIFESP] (2016)
This work intends to analyze the formation of the Military Police of the State of São Paulo (Polícia Militar do Estado de São Paulo) during the military dictatorship. Focusing on the period between the 1964 coup and the first direct state government election in 1982, it seeks, first, to understand the factors that lead to the unification of the Civil Guard (Guarda Civil) and Public Force (Força Pública), giving origin to the Military Police. The state public security structure is described and disputes involving the corporations and other social and political agents around reform propositions are analyzed. After the coup, the federal government increased the pressure for the unification in a single military corporation in uniform. Disputes between the Civil Guard and the Public Force increased until, amid the growing of the armed struggle and the hardening of the regime, the dictatorship imposed the unification of these corporations, giving origin to he Military Police. The unification did not follow only pragmatic organizational criteria; it also had an ideological orientation. The thesis examines how the "revolutionary war" doctrine, developed in France to fight national liberation movements in its colonies, was assimilated by the Brazilian dictatorship and used to orient police reorganization. From the start, the doctrine was systematically introduced in Military Police school programs, giving great emphasis to espionage and counter-insurgency tactics. Based on this, shock-troop and intelligence units rose to predominance in the Military Police, growing in number and influence within the corporation.